تاثير منهج تدريبي للقوة المميزة بالسرعة واداء بعض المهارات الاساسية بكرة السلة - عمر عبد الغفور عبد الحافظ (الرياضة المعاصرة, 2018)
A search on the four-door broken down as follows 1. A search on the simple introduction about the game of basketball and the research problem and objectives of the research, including (a training curriculum to develop distinctive force the speed and performance of some of the basic skills of basketball), as well as the imposition of research (there are significant differences between tribal tests and a posteriori and in favor of the post tests in the distinctive strengths differences the speed and performance of some of the basic skills of basketball with the research sample) also included a sample search on the (12) players from club students basketball. 2. ensure that the door presentation of the results of statistical processing using a set of tables, and then analyzed and discussed in a scientific manner accurate and supported by scientific sources through this discussion and then to reach the goals of the research and verification of the hypothesis. 3. Conclusion included the conclusions of which (helped organize performances and doing exercises on according to prepared curriculum by the researcher at the research sample to raise the level of performance of some of the basic skills and this afternoon through the results a posteriori) and the recommendations of which (emphasize the importance of your skills preparation and their role stage in the development level physical and technically gifted and reflection in achieving positive results).